Physicochemical Properties of Golden Apple Snail (Pomacea canaliculata) Shell Chitosan - Larasati Sekar Ayu; Dedin Finatsiyatull Rosida; Jariyah; Teeradate Kongpichitchoke; Anugerah Dany Priyanto; Andre Yusuf Trisna Putra (Food Science and Technology Journal (Foodscitech), 2023)
The golden snail (Pomacea canaliculata) is an animal that lives in rice fields and is one of the agricultural pests that often suffers and can interfere with the growth of rice plants because of its very fast development. unused and become waste for the environment. The golden snail shell contains a chitin polysaccharide which can be reduced to chitosan (β1-4 N-acetyl D-glucosamine) through the deacetylation stage, namely the process of taking the acetamide group in chitin (CH3CONH) so that it becomes an amine group (NH2) in chitosan. The manufacture of chitosan is carried out through 3 stages, namely the process of deproteination, demineralization, and deacetylation. The purpose of this study was to determine the characteristics and quality of chitosan produced from golden snail shells. Based on the analysis conducted, chitosan has a yield of 53.91%; water content 1.68%; ash content 12.31%; molecular weight 640.83 kDa; solubility 95.53; and deacetylation degree 82.33%.